Principles of structural design : wood, steel, and concrete - Gupta, Ram S. (CRC Press, 2011)
Anyone involved with structural design, whether a student or a practicing engineer, must maintain a functional understanding of wood, steel, and concrete design principles. In covering all of these materials, Principles of Structural Design: Wood, Steel, and Concrete fills a gap that exists in the instructional resources. It provides a self-contained authoritative source that elaborates on the most recent practices together with the code-connected fundamentals that other books often take for granted.
Keywords: Structural design.; Building materials.; Steel, Structural.; Wood.; Concrete.; elektronické knihy; electronic books